Building Longitudinal Datasets From Diverse Historical Data in Australia - Janet McCalman (Historical Life Course Studies)
Australia is rich in population datasets generated to manage convicts, civilians, stock, land and the colonised and displaced First Nations people. It has also preserved all service and pension data from both world wars. Through nominal linkage using volunteers and paid research staff, it has been possible over the past twenty years to build four cradle-to-grave datasets derived from administrative cohorts: poor white babies born in a charity hospital 1858–1900; Aboriginal Victorians from 1855 to 1988; convicts transported to Van Diemen’s Land 1818-1853 and servicemen who embarked for World War I from the State of Victoria. The abundance of digitised historical sources from government archives to historical newspapers enables the practice of demographic prosopography, with a wide range of variables that have yielded new insights into Australia’s population and social history.